Crystallization of a potassium ion channel and X‐ray and neutron data collection. Issue 6 (17th June 2019) - Langan, Patricia S.; Vandavasi, Venu Gopal; Sullivan, Brendan; Harp, Joel; Weiss, Kevin; Coates, Leighton
Abstract : The growth of a large crystal of a potassium ion channel, and neutron and X‐ray data collection from the crystal are described. Abstract : The mechanism by which potassium ions are transported through ion channels is currently being investigated by several groups using many different techniques. Clarification of the location of water molecules during transport is central to understanding how these integral membrane proteins function. Neutrons have a unique sensitivity to both hydrogen and potassium, rendering neutron crystallography capable of distinguishing waters from K + ions. Here, the collection of a complete neutron data set from a potassium ion channel to a resolution of 3.55 Å using the Macromolecular Neutron Diffractometer (MaNDi) is reported. A room‐temperature X‐ray data set was also collected from the same crystal to a resolution of 2.50 Å. Upon further refinement, these results will help to further clarify the ion/water population within the selectivity filter of potassium ion channels.